Economy Circular Adoption toward Sustainable Business (Study case: Agro-industry Company in Indonesia) - Marthalia, Lusye; Tumuyu, Sri Setiawati; Asteria, Donna (Pusat Penelitian Lingkungan Hidup, IPB (PPLH-IPB) dan Program Studi Pengelolaan Sumberdaya Alam dan Lingkungan, IPB (PS. PSL, SPs. IPB), 2024)
Agroindustry is one of industrial sector that considered important to adopt the Circular Economy (CE) principles, considering its close relation with agriculture and food system, and its significant contribution to the transition of low-carbon economy. In principle, the CE adoption on agroindustry, mostly focus on resource efficiency, waste management, energy efficiency and their collaborative cooperation with stakeholders. Business sector in general, are facing many challenges and obstacles to overcome the complexity for integrating business processes, supply chains and collaboration between stakeholders align with corporate’s business strategy for implementing CE. The purpose of this study is to analyse the CE adoption at micro level at agroindustrybusiness refer to their own business character. This article using the two indicator reference, firstly EMF Circulytics 2.0 (TheEllen MacArthur Foundation) that explores corporate circularity and secondly the 10R CE principles that are often being used as general CE framework. The expected outcome from this article is to open wider insights regarding CE adoption in agroindustry corporate strategy as the transformative business model innovation towards sustainable development.